Development of transport and logistics infrastructure in the Republic of Kazakhstan - Шарапиева, М. (Journal of Economic Research & Business Administration, 2017)
The modernization of logistics and logistics systems occupy a special role in the improvement of the transport system, as well as the entire range of services for fast and high-quality delivery of goods. Important strategy for international logistics management in global markets is the clarity and high speed processing transactions. The relevance of logistics becomes a key point in developed societies. Transport logistics occupies a strategic role in the industrial development of the Republic of Kazakhstan. Carrying out the movement of goods and passengers, transport accounts for some work and ensures optimum distribution of productive forces and the rationalization of economic ties. This article shows the current state of the logistics market in the Republic of Kazakhstan. Transport logistics is one of the conditions for the successful implementation of the forced industrialization of the country.